A rare case of acute paraplegia: primary Ewing’s Sarcoma of dorsal spine - N. N. T., Yeshwant Kumar; Rajan, V. T. T. (International Surgery Journal, 2018)
Ewing’s sarcoma is a primary bone malignancy with the highest incidence in the second decade of life. Although it mostly affects the metaphyseal region of long growing bones, involvement of spine is not very uncommon especially the sacrum. Non-sacral spinal Ewing’s sarcoma is rarer and often mimics a benign condition before spreading extensively. They present with neurologic deficits due to spinal cord compression, but acute onset paraplegia has not been previously reported. A high index of clinical suspicion can clinch the diagnosis early in the course of the disease. A prompt intervention is required to keep neurological damage to a minimum, and a correct combination of surgery, chemotherapy, and radiotherapy is required for better long-term patient outcome. We report a 11-year-old female who presented with acute paraplegia and had an excellent postoperative outcome after radical excision of a C7-D2 Ewing’s sarcoma.